Incidence and Determinants of Chemotherapy Associated Thromboembolic Events among Ethiopian Patients Treated for Solid Malignancy: A Retrospective Cross-Sectional Study. (April 2022) - Yabeyu, Abdella Birhan; Hussen, Shemsu Umer; Tigneh, Wondemagegnhu; Fentie, Atalay Mulu
Venous thromboembolism is a common problem in patients treated for cancer, although the reported incidence varies widely between studies. This was the first study in its kind in Ethiopia and aimed to assess the incidence and determinants of chemotherapy associated thromboembolic events among patients treated for solid malignancy. An institution-based retrospective cross-sectional study was conducted from 1st March to 1st June, 2019 at adult oncology center of Tikur Anbessa Specialized Hospital. Systematic random sampling technique was employed to recruit 423 study participants. Patients who have received at least a single cycle of any chemotherapy regimen were included in the study. Khorana risk assessment tool was used to predict chemotherapy associated thrombosis. Descriptive statistics were used to summarize the data while multivariable logistic regression was employed to explore associations among variables of interest. The median age of study participants was 43 years, which ranged from 14 to 83 years. Majority of the study participants were treated for breast cancer. Thromboembolic events encountered in 43(10.2%) of patients, from which the commonest one being deep venous thrombosis 36 (85.7%), followed by myocardial infarction 5(11.9%). In multivariable logistic regression, blood transfusion, a primary site of cancer with gastrointestinal malignancy and performance status showed statistically significant association towards the occurrences of thromboembolic events. The incidence of chemotherapy associated thromboembolic events among patients treated for solid malignancy was comparable to other studies. Hence, other prospective randomized trials are needed to see the importance of thrombo-prophylaxis in such high-risk patients.